If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8x-12=-9(x+7)
We move all terms to the left:
8x-12-(-9(x+7))=0
We calculate terms in parentheses: -(-9(x+7)), so:We get rid of parentheses
-9(x+7)
We multiply parentheses
-9x-63
Back to the equation:
-(-9x-63)
8x+9x+63-12=0
We add all the numbers together, and all the variables
17x+51=0
We move all terms containing x to the left, all other terms to the right
17x=-51
x=-51/17
x=-3
| 7y=8y-3+3y-4y+5 | | 4±1m=12±2m. | | -7x+2(6x+10)=70 | | 3(k-3)-7=3k-(2k-1) | | 3h=5h+18 | | 13+9y=-14 | | 2/3m+6=2/3(m+9) | | 4a-2=4(a+1)+10a+5 | | -3x+4.5x=15 | | 5x-4(-6x-20)=-239 | | F(x)=x+5/10-2x | | 160+x=3x | | 4x^2+5x=84 | | (9x-5)=(4x+3) | | 4(x-2)-3x=-8 | | 3x^2+7x=66 | | -3.3x=-1.1 | | 1/4(p+9)-7/5(p+7)=-11 | | 1/1.5=x/8 | | 2(2p+3)=6 | | -6x-4(-6x-13)=178 | | 8x-(6x+8)=3x-24 | | 13+6n-14+19n=0 | | 13+6n-14+19=0 | | 3(2x–1)–2=2(x+7)+1 | | (2v+5)*(3+v)=0 | | 2/5(15x-10)=5x+11 | | 11j=18j-7 | | -6.5c=12.96-1.1c | | -10-5h=-3h | | 20=40-2.5r÷.5 | | -2-16y=-11y-15-6y |